Combining Locoregional Therapies in the Treatment of Hepatocellular Carcinoma - Higgins, Mikhail C. S. S.; Soulen, Michael C. (Seminars in Interventional Radiology, 2013)
In an effort to promote more durable local control of larger lesions, thermal ablation has been combined with chemical ablative techniques and with vaso-occlusive procedures such as chemoembolization and bland embolization in an effort to mitigate the limitations inherent in the use of any single treatment for hepatocellular carcinoma (HCC) >3 cm. The heat-sink effect is the underlying principle for combining vaso-occlusive therapies with ablative techniques. Combination therapies do present viable options for abrogating tumor progression and potentially downsizing tumors to facilitate transplant. We discuss the two most commonly used combination locoregional therapies by the interventionalist and the evidence defining the best techniques in practice.
Keywords: interventional radiology; hepatoma; ablation; chemoembolization; combination therapy